Identification of mouse colony-forming endothelial progenitor cells for postnatal neovascularization: a novel insight highlighted by new mouse colony-forming assay - Tsukada, Shizu (BioMed Central, 2013)
INTRODUCTION: Endothelial progenitor cells (EPCs) play a critical role in restoration of ischemic diseases. However, the actual status of EPC development and the mechanisms of EPC dysfunctions in patients with various ischemic diseases remain unknown. METHODS: To investigate the detailed function of EPCs in experimental murine models, we have established an EPC colony forming assay (EPC-CFA) in murine EPCs. The abilities of murine EPCs in differentiation, adhesive capacity, proliferative potency, and transplantation in vitro and in vivo were then examined. RESULTS: Peripheral blood mononuclear cells (PB-MNCs), bone marrow mononuclear cells (BM-MNCs) or bone marrow c-Kit(+)/Sca-1(+ )lineage negative (BM-KSL) cells differentiated into two types of EPC colony forming units (EPC-CFUs), large sized EPC (large-EPC)-CFUs and small sized EPC (small-EPC)-CFUs. Gene expression analysis demonstrated that both EPC-CFU-derived cells expressed eNOS, Flk-1 and VE-cadherin, markers of endothelial cells (ECs), although the small-EPCs derived from small-EPC-CFU were higher in number and showed more immature features (higher population of KSL cells). Functionally, the large-EPCs derived from large-EPC-CFU had higher adhesive capacity but lower proliferative potency than small-EPCs, showing improved tubular forming capacity and incorporation potency into primary EC-derived tube formation. Importantly, hindlimb ischemia increased the frequencies of large-EPC-CFUs differentiated from PB-MNCs and bone marrow. Actually, transplantation of large-EPCs into ischemic hindlimb enhanced neovascularization in hindlimb ischemia model, although small-EPCs or murine ECs did not, suggesting that large-EPC-CFUs might play an important role in restoration of ischemic diseases. CONCLUSIONS: We demonstrated, using a murine ischemia model, that the EPC-CFA could be a useful way to investigate the differentiation levels of murine EPCs, further providing a crucial clue that large-EPC-CFU status may be more functional or effective EPCs to promote neovascularization.